(untitled) (Semiárida, 2020)
The objectives of this study were to evaluate the forage yield, protein content and seed yield of pampean bromegrass, rescue gran, and intermediate bromegrass experimental Iines. The cultivar "Don Lorenzo INTA" of intermediate bromegrass was used as reference. Two randomized complete block designs with 4 replicates were done, one for forage yield and protein contentand the other for seed yield and 1000 seed weight. ANOVA and FLSO tests (p<0,05) were also performed. L1nesof the three species shown similar forage yield and protein content, thus all of them should be considered to be Improved through plant breeding. Intermediate bromegrass showed lower seed production than the other. This character is a disadvantage to get a success with natural reseeding. The cultivar "Don Lorenzo INTA" of Intermediate bromegrass showed Intermediate values in forage and seed yields.